Bambusiform grasses (Poaceae) from the Los Amigos River, Madre de Dios, Peru - Olivier, Jean (2008)
This note offers to know the species of bambusiform Poaceae (Gramineae) present in and around the Los Amigos River Concession for Conservation, in the Madre de Dios, basin the southern part of the Peruvian Amazonia. It supply keys and illustrated material for identification of the taxa present within the area.